Effect of Cadmium on Phenolic Compounds, Antioxidant Enzyme Activity and Oxidative Stress in Blueberry (Vaccinium Corymbosum L.) Plantlets Grown in Vitro - Escudey-Castro, A; Escudey-Castro, A; Zuniga-Navarro, G; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Academic Press, 2016)
Cadmium (Cd2+) can affect plant growth due to its mobility and toxicity. We evaluated the effects of Cd2+ on the production of phenolic compounds and antioxidant response of Vaccinium corymbosum L. Plantlets were exposed to Cd2+ at 50 and 100 µM for 7, 14 and 21 days. Accumulation of malondialdehyde (MDA), hydrogen peroxide (H2O2) and the antioxidant enzyme SOD was determined. The profile of phenolic compounds was evaluated using LC-MS. The antioxidant activity was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and the ferric reducing antioxidant power test (FRAP). Cd2+ increased the content of MDA, with the highest increase at 14 days. The presence of Cd2+ resulted in changes in phenolic compounds. The main phenolic compound found in blueberry plantlets was chlorogenic acid, whose abundance increased with the addition of Cd2+ to the medium. The changes in the composition of phenolic compounds showed a positive correlation with the antioxidant activity measured using FRAP. Our results suggest that blueberry plantlets produced phenolic compounds with reducing capacity as a selective mechanism triggered by the highest activity of Cd2+. © 2016 Elsevier Inc.